Soil Microbial Diversity and It’s Technology to Promote Sustainable Agroecosystem - Kabita Budthapa; Prof. Dr. Iin Handayani, MSc (Journal of Smart Agriculture and Environmental Technology, 2026)
Soil is home to a vast array of microorganisms that are essential to ecosystem multifunctionality (EMF), which includes climate regulation, organic matter breakdown, and nutrient cycling. This literature review summarizes the state of knowledge regarding how soil microbial diversity affects agricultural ecosystem services and functions, emphasizing important processes including phosphorus solubilization, nitrogen fixation, and nutrient mobilization. It describes the ideas of functional redundancy and niche complementarity, which help ecosystems remain stable and resilient in the face of  environmental stress. In addition, it also examined the anthropogenic forces that affect soil microbial communities, such as pollution and land-use change. This article describes the biotic and abiotic drivers of microbial diversity. The promise of methodological  advancements like machine learning, stable isotope probing, and omics technologies to expand the understanding of soil microbial ecology is investigated. To maximize microbial potential for environmental resilience and sustainable development, we provide the review of promoting new emerging technology for microbial diversity identification and policy integration. Overall, this article shows the importance of preserving and managing soil microbial diversity to promote sustainable agriculture, enhance soil health, and reduce the effects of climate change.